2020
DOI: 10.1002/14651858.cd013520
|View full text |Cite
|
Sign up to set email alerts
|

Topical pharmacologic interventions versus placebo for epidemic keratoconjunctivitis

Abstract: Topical pharmacologic interventions versus placebo for epidemic keratoconjunctivitis (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…One-year follow-up showed that the 60% size and number of SEIs were decreased after six-month administration of tacrolimus ointment or drops and were eliminated in 32%. The visual acuity was improved significantly following the treatment procedure [17,18]. Stopping the drug administration for seven months caused a recurrence of almost 19% of the eyes [18].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…One-year follow-up showed that the 60% size and number of SEIs were decreased after six-month administration of tacrolimus ointment or drops and were eliminated in 32%. The visual acuity was improved significantly following the treatment procedure [17,18]. Stopping the drug administration for seven months caused a recurrence of almost 19% of the eyes [18].…”
Section: Resultsmentioning
confidence: 98%
“…The visual acuity was improved significantly following the treatment procedure [17,18]. Stopping the drug administration for seven months caused a recurrence of almost 19% of the eyes [18]. Interferon-b, an immunomodulator secreted by virally infected cells, may act by inducing an antiviral state or modulating the immune response [19].…”
Section: Resultsmentioning
confidence: 99%